The Influence of Renewable Energy Sources on the Czech Electricity Transmission System - Karel Janda; Jan Malek; Lukas Recka (Charles University in Prague, Institute of Economic Studies (IES), 2017)
This paper provides the first academic economic simulation analysis of the impact of increase in predominantly German wind and solar energy production on the Czech electricity transmission network. To assess the exact impact on the transmission grid, updated state-of-the-art techno-economic model ELMOD is employed. Two scenarios for the year 2025 are evaluated on the basis of two representative weeks. The first scenario is considered as baseline and models currently used production mix. The second scenario focuses on the effect of German Energiewende policy on the transmission networks as expected in 2025. The results confirm that higher feed-in of solar and wind power increases the total transport of electricity between transmission system operator areas as well as the average load of lines and volatility of flows. Also, an increase in number of critical high-load hours is observable. Taking into account only the Czech transmission system, considerable rise both in transported volume and volatility are observed only on border transmission lines, not inside the country. Moreover, our qualitative analysis shows that all these mentioned effects are strenghtened by the presence of German-Austrian bidding zone.
Keywords: L94; Q21; Q48; C61; 330; Energiewende; wind; solar; transmission networks; ELMOD